Knowledge of Farm Women regarding Various Agricultural Activities - Shaikh, J. I.; Shinde, S. B. (Journal of Agricultural Extension Management, 2019)
The international development community has recognized that agriculture is an engine of growth and poverty reduction in countries where it is the main occupation of the poor. However, the agriculture sector in many developing countries is underperforming, in part, because women, who represent a crucial resource in agriculture and the rural economy through their roles as farmers, laborers and entrepreneurs, almost everywhere face more severe constraints than men in access to productive resources. The knowledge of farm women regarding various agricultural activities was higher namely in bird watching, harvesting, intercultural operations and lower in land preparation activities, marketing, post-harvest operations, seed bed preparation and processing activities. Majority (71.50 %) of the respondents had medium level of knowledge about the different agricultural activities followed by 25.50 per cent and 3.00 per cent of the respondents with low and high level of knowledge respectively.